Effect of ultrasonic low - frequency vibration and its direction on machinability in WEDM process. Issue 9 (4th July 2022) - Phan, Nguyen Huu; Muthuramalingam, T.; Trong Ly, Nguyen; Van Dua, Tran
ABSTRACT: It is important to analyze and improve quality measures in such process. In this investigation, an analysis was made on finding the influence of vibrational direction with respect to cutting direction on quality measures while machining SKD 61 steel using wire EDM process. The material erosion rate, kerf width and surface roughness were considered as the response parameters to evaluate the machinability. Taguchi-DEAR-based optimization approach was utilized to further improve the quality measures in EDM process. The parallel direction vibration could produce higher material exclusion with lower surface roughness and kerf width in low-frequency-assisted wire electrical discharge machining process owing to efficient deionization and larger contact area. The optimal process factors in V-WEDM process were computed as F (500 Hz), GV (80 V), Ton (1 µs) and Toff (20 µs) among the chosen parameters. It was also inferred that vibration frequency could enhance the quality measures due to its importance on flushing process. Graphical abstract: uf0001